Clinical consensus document for fitting non-surgical transcutaneous bone conduction hearing devices to children. - Bagatto, Marlene; Gordey, Dave; Brewster, Lynne; Brown, Christine; Comeau, Michael; Douglas, Charlotte; El-Naji, Rana; Fortier, Sheila; Gascon, Alex; Godovin, Jessica; Ittner, Colleen; Magathan Haluschak, Meredith; et al. (International Journal of Audiology, 2022)
This clinical consensus document addresses the assessment, selection, and fitting considerations for non-surgical bone conduction hearing devices (BCHD) for children under the age of 5 years identified as having unilateral or bilateral, permanent conductive or mixed hearing losses. Children with profound unilateral sensorineural hearing losses are not addressed. The document was developed based on evidence review and consensus by The Paediatric Bone Conduction Working Group, which is composed of audiologists from North America who have experience working with BCHDs in children. The document aims to provide clinical direction for an area of paediatric audiology practice that is under development and is therefore lacking in standard protocols or guidelines. This work may serve as a basis for future research and clinical contributions to support prospective paediatric audiology practices.